Not the killing type [large type] - Barrett, Lorna (Barrett, Lorna. Booktown mystery., 2013)
In Stoneham, New Hampshire, it's time for the Chamber of Commerce elections. The race is heated, as the long-standing Chamber president is being challenged by a former lover -- bookstore owner Tricia Miles' sister. Then business owner Stan Berry throws his hat in the ring. But it's not there long when he's found murdered in the Brookview Inn with a brass letter opener belonging to the receptionist, who Tricia knows is no killer.